2024
DOI: 10.1097/gox.0000000000005575
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ChatGPT 3.5 as a Tool to Optimize Readability of Patient-facing Craniofacial Education Materials

Medha Vallurupalli,
Nikhil D. Shah,
Raj M. Vyas

Abstract: Background: To address patient health literacy, the American Medical Association recommends that readability of patient education materials should not exceed a sixth grade reading level; the National Institutes of Health recommend no greater than an eigth-grade reading level. However, patient-facing materials in plastic surgery often remain at an above-recommended average reading level. The purpose of this study was to evaluate ChatGPT 3.5 as a tool for optimizing patient-facing craniofacial educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, one study identified that in plastic surgery, 50.2% of patients had an education level lower than high school and that 48% of attendings, residents, and PAs said it was challenging to make patients follow postoperative instructions [ 34 ]. Moreover, patient materials in plastic surgery are often above the recommended average reading level of 6th to 8th grade and may be too difficult for the average patient [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one study identified that in plastic surgery, 50.2% of patients had an education level lower than high school and that 48% of attendings, residents, and PAs said it was challenging to make patients follow postoperative instructions [ 34 ]. Moreover, patient materials in plastic surgery are often above the recommended average reading level of 6th to 8th grade and may be too difficult for the average patient [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vallurupalli et al [ 37 ] successfully used ChatGPT-3.5 to significantly simplify traditional patient education materials for craniofacial surgery by 3 FKGL points. Interestingly, in our study, ChatGPT-3.5 and 4’s average FKGL scores were far superior to the recommended reading level.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic surgery is a field of innovation where new techniques and research findings regularly emerge to improve patient-centered outcomes [ 14 , 15 , 16 ]. LLMs have been used in aesthetic surgery, general plastic surgery, craniofacial, microsurgery, and hand surgery, where they have displayed adequate knowledge for research proposals, patient counseling, clinical decision-making, and intraoperative support [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. To evaluate ChatGPT’s knowledge of plastic surgery, Humar et al [ 28 ] prompted the questions from the 2022 In-Service Examination, where the model surprisingly ranked in the 49th percentile for 1st-year integrated plastic surgery residents.…”
Section: Introductionmentioning
confidence: 99%